THE USE OF MIND MAPPING TECHNIQUE IN INCREASING STUDENTS’ WRITING SKILL ON DESCRIPTIVE TEXT THROUGH MINDOMO APPLICATION FOR SECOND GRADE OF SMAN 3 TEUPAH SELATAN - Riski Mayusandra; Rosdiana Rosdiana; Syarfuni Syarfuni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to determine the use of the mind mapping technique through the mindomo application to improve students' writing comprehension focused on descriptive text in eleventh grade at SMA Negeri 3 Teupah Selatan 2023/2024 and to find out whether the use of the mind mapping technique through the mindomo application can improve students' writing comprehension of texts descriptive text in eleventh grade at SMA Negeri 3 Teupah Selatan. This class consists of 19 students. The author believes that using the mind mapping technique through the mindomo application can be chosen as one of the effective efforts used to overcome students' writing comprehension in the teaching and learning process. In this study, the writer will see whether the use of mind mapping techniques through the mindomo application can improve students' writing comprehension of descriptive texts. From the research, the authors found that there was a significant influence on student scores before and after the experiment. The results showed that the students' post-test scores increased significantly the highest compared to the pre-test. Based on the explanation above, it can be concluded that the accepted hypothesis states that the use of the mind mapping technique through the Mindomo application can increase students' scores in understanding writing descriptive text.